Making it : manufacturing techniques for product design - Lefteri, Chris (London : Laurence King Publishers, 2007)
There are many different ways in which a product can be manufactured, but most designers probably know only a handful of techniques in any detail. Using contemporary design as a vehicle to describe production processes, this book covers a broad range of almost 90 production methods with descriptive text, specially commissioned diagrams, product shots, and photographs of the manufacturing process. It will appeal not only to product designers involved in lighting, consumer electronics, packaging, domestic accessories and tableware, but also to interior designers, furniture and graphic designers who need access to a range of production methods, as well as to all students of design.
Keywords: Industrial design; Manufacturing processes